Nutrition, growth and reproduction of the Asian water buffalo (Bubalus bubalis) - M. R., Jainudeen; Abdullah, Hilmi; Syed Salim, Syed Jalaludin (1978)
The water buffalo has received very little attention despite its contribution to farm power, milk and meat. Since the buffalo thrives under adverse conditions utilizing fodder of low nutritive value, unique features of its nutrition are reviewed. Buffaloes grow faster than cattle managed under similar feeding conditions. There are no differences in carcass characteristics between buffaloes and cattle. However, the buffalo produces a leaner than cattle. There is a need to exploit the meat producing ability of the buffalo in future livestock enterprises. With techniques to induce estrus and fixed time insemination, artifical insemination in the swamp buffalo can now be practised on a larger scale.